2010
DOI: 10.1007/s12522-010-0066-1
|View full text |Cite
|
Sign up to set email alerts
|

Serum anti‐Müllerian hormone level as a predictor of poor ovarian response in in vitro fertilization patients

Abstract: Purpose To evaluate the clinical value of day 3 serum anti-Müllerian hormone (AMH) compared with day 3 serum follicle-stimulating hormone (FSH) and human chorionic gonadotropin (hCG) day estradiol (E2) levels and antral follicle count (AFC) in the prediction of poor ovarian response in controlled ovarian hyperstimulation (COH). Methods AMH, FSH and AFC on day 3 as well as hCG day E2 levels were determined in 164 subjects. Receiver operating curve analyses and area under curves (AUC) of the study parameters wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 34 publications
2
16
0
Order By: Relevance
“…In our previous study we found that an AMH cut-off level of 2 ng/ml could predict poor response with a sensitivity of 78.9% and specificity of 73.8% [32]. In another study we found that an AMH cut-off level of 3.3 ng/mL predicted ovarian hyperstimulation syndrome (OHSS) with a sensitivity of 90% and a specificity of 71%.…”
Section: Discussionmentioning
confidence: 95%
“…In our previous study we found that an AMH cut-off level of 2 ng/ml could predict poor response with a sensitivity of 78.9% and specificity of 73.8% [32]. In another study we found that an AMH cut-off level of 3.3 ng/mL predicted ovarian hyperstimulation syndrome (OHSS) with a sensitivity of 90% and a specificity of 71%.…”
Section: Discussionmentioning
confidence: 95%
“…A relatively new marker, anti-müllerian hormone (AMH) was evaluated by several study groups as a marker of ovarian response [10,11]. AMH, a member of the transforming growth factor-beta super-family, is mainly secreted by the granulosa cells of ovarian early developing follicles.…”
Section: Introductionmentioning
confidence: 99%
“…It also has minimal inter-and intracycle variability [6,7]. In clinical practice, it is useful for the prediction of poor responders [8] and ovarian hyperstimulation syndrome (OHSS) [9]. Moreover, it is positively correlated with pregnancy rates [10,11].…”
Section: Introductionmentioning
confidence: 99%